Determination of the value of glycated hemoglobin HbA1c and fructosamine in assessing the risk of perioperative complications after cardiac surgery in patients with type 2 diabetes - Kowalczuk-Wieteska, Anetta M.; Wróbel, Marta; Rokicka, Dominika; Szymborska-Kajanek, Aleksandra; Foremny, Jerzy; Nadziakiewicz, Paweł; Zembala, Marian; Strojek, Krzysztof (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Introduction : Patients with diabetes have a worse postoperative course and longer length of hospital stay after surgery. A good indicator of proper long-term (3 months) glycemic control is glycated hemoglobin (HbA 1c ), and fructosamine in the short term (2–3 weeks). Aim : To determine the degree of glycemic control evaluated preoperatively by HbA 1c and/or fructosamine influence on the postoperative course of patients with diabetes undergoing coronary artery bypass grafting (CABG) in 2014–2015. Material and methods : Before the operation HbA 1c (N < 7.0) and fructosamine (N < 280 μmol/l) were measured and depending on the results the respondents were divided into 4 groups: group I (n = 46) – normal both parameters; group II (n = 22) – high both values; group III (n = 4) – normal fructosamine/HbA 1c high; group IV (n = 33) – high HbA 1c /fructosamine normal. Statistical analysis was performed using the t-test assuming p < 0.05 to be statistically significant. Results: One hundred and five patients were treated by CABG/OPCAB (39 female, 66 males). The mean age was 65.7 ±7.3, HbA 1c : 7.23 ±1.2%, fructosamine: 261.8 ±43.8. There was no difference in the incidence of other postoperative complications between the two groups. Conclusions: Glycated hemoglobin and fructosamine levels to a similar extent define the risk of perioperative complications in patients undergoing cardiac surgery. In patients in whom there is a need to quickly compensate for elevated blood glucose consider enabling determination of fructosamine.